Avaliação da resistência ao deslocamento de dois cimentos endodônticos acrescidos de nanopartículas de clorexidina - Labanca, Marta Reis da Costa (2017)
The aim of the present study was to evaluate the bond strength of two endodontic sealers: AH Plus (Dentply, DeTrey, Konstanz, German) and MTA Fillapex (Angelus, Londrina, Paraná, Brazil) when has added in its formulation with 2% of chlorhexidine nanoparticles. The endodontic sealers MTA Fillapex and AH Plus were used in their original formulation as reference materials for comparison. Fifteen human permanent upper central incisors were selected and two dentin slices (1 ± 0.1 mm thick) were obtained from the cementoenamel junction of each root. Two 0.8 mm diameter holes were made in each dentin slice. Samples were given standard irrigation and were dried with absorbent paper. Then, each of the holes was filled with one of the evaluated endodontic sealers and stored in a humidified environment with phosphate-buffered saline solution (pH 7.2) for 7 days at 37°C. After storage, a push-out test was performed. The Kruskal-Wallis test and Mann Whitney test were used to evaluate the displacement resistance of the tested endodontic sealers. The Bonferroni multiple correction test (α = 5%) was used to isolate the differences. The results of the present study show that the samples filled with AH Plus (AH Plus and AH Plus-CHX) had the highest dentin bond strength values (p <0.05) when compared to the MTA Fillapex filled samples Fillapex and MTA Fillapex-CHX). The incorporation of CHX nanoparticles did not influence the bond strength of the tested materials (p > 0.05). The present study allows to conclude that the incorporation of a chlorhexidine-based nanoparticulate antimicrobial agent did not affect the displacement resistance of the AH Plus and MTA Fillapex endodontic sealers.